The Feasibility Study of Innovative Public Policy Client-Accordance Index - Putans, Romans (IIAS Study Group on ‘Coproduction of Public Services’, 2019)
The role of the societies and their interaction with public administration is changing toward ever closer cooperation. Since 2009 scientific literature, and to a lesser extent also the public administrations themselves, have increasingly been exploring the changing and dynamic role of the recipient of public services, or the client, as that of a partner in the provision of public services. In scientific literature this phenomenon is described as the concept of co-production or co-creation of public services. This is foreseen as the next stage of evolution in the relationship between public administration and society. With growing and wide-ranging social and civil participation in overall public governance, it is inevitable that new tools and approaches will be needed to facilitate the cooperation and co-production between policy makers and society itself. Furthermore, similar growing tendencies and principles of closer cooperation between providers and recipients can also be found business sector, most visibly in e.g. social entrepreneurship and crowdfunding. This, in turn, can give additional lessons to learn from in understanding the possible developments of the co-production of public services. Author`s proposed policy client-accordance index (PCA index), which measures the relevance of policy planned results and policy-makers’ expectations in relation to clients` intentions, is a draft try to contribute to this necessity. Such a research to large extent tackles also the general problem of insufficiency of innovation in public governance. The main goal of the research is to set for the experts` discussion on the applicability and challenging aspects of the feasibility and to test the possible transfer of the author`s developed Latvian youth policy case-based policy client-accordance evaluation methodology model for evaluating the relevance of any public administrations` policies to the intentions of the policy`s respective client target group – the client-accordance index of a given public policy. The research design essentially consists of 1) selection of public policy areas, 2) identification of main policy intentions and expectations, including the review of methodologies to do so, 3) categorizing the segments of the respective policy`s clients` target groups. To conduct the research on these stages, the contents analysis of respective legislative acts and expert interviews are to be conducted. The fourth stage of research design shall be 4) setting of the methodologies to collect the respective policy`s clients` target group intentions and evaluations with regard to the co-production process in the public governance in the respective policy area. Large focus of the research is planned to be put on the usage of existing data or collection of data for clients`/co-producer`s profiling – their interests, intentions, needs. The uncertain concept of the big-data, the risks of the surveillance state as well as the certain concerns of data privacy issues in relation to state information registers shall be reviewed. The research methods includes, firstly, scientific literature analyses to review the applications of relevant theories, experts` discussions and analyses of several empirical studies in EU countries. The literature research and experts` discussions forms the basis of creating the draft typology and structure of public policies, its respective services` groups, client target groups, and client-based approaches as an integral part of co-production. Then the feasibility of the author`s developed youth policy case study based client-accordance index methodology model shall be analysed. The main expected outcome of the research is the classification of typology of public policies, their respective services, client groups, and most importantly adjusted feasibility methodologies of client-accordance index measurement showing the integrity level of coproduction of public services.
This research paper was presented at the KU Leuven Public Governance Institute IIAS Study Group on ‘Coproduction of Public Services’ seventh annual conference, Leuven, Belgium, 28 May 2019.
Keywords: Research Subject Categories::SOCIAL SCIENCES; public administration; cocreation; public services; client-accordance index